'Voyage to the moon' and other imaginary lunar flights of fancy in antebellum America - Gutjahr, Paul C. (Anthem nineteenth century studies., 2018)
'Voyage to the Moon' And Other Imaginary Lunar Flights of Fancy in Antebellum America offers critical textual editions with introductions, explanatory footnotes and appendixes of the four moon voyage stories written by Americans before the Civil War.